(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to examine the effect of audit quality and ownership structure on earnings management through real activities. The audit quality tested is the size of the public auditor’s office and auditor independence. The ownership structure that has been examined for its impact on management management is institutional ownership, managerial ownership, and foreign ownership. Earnings management through real activities is measured by three methods, namely abnormal cash flow from operation (CFO), abnormal discretionary expense, and abnormal production cost. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2018. With the purposive sampling method, the final sample is 175 company-years. The results showed that auditor quality and ownership structure had no effect on earnings management as measured by abnormal CFO. Meanwhile, abnormal production cost is not proven to be influenced by ownership structure but is negatively affected by audit quality as measured by Auditor Firm size. Ownership structure and audit quality are proven to have an effect on earnings management, which is measured by abnormal discretionary expense.